Multi-objective control for cooperative payload transport with rotorcraft UAVs. (September 2018) - Gimenez, Javier; Gandolfo, Daniel C.; Salinas, Lucio R.; Rosales, Claudio; Carelli, Ricardo
Abstract: A novel kinematic formation controller based on null-space theory is proposed to transport a cable-suspended payload with two rotorcraft UAVs considering collision avoidance, wind perturbations, and properly distribution of the load weight. An accurate 6-DoF nonlinear dynamic model of a helicopter and models for flexible cables and payload are included to test the proposal in a realistic scenario. System stability is demonstrated using Lyapunov theory and several simulation results show the good performance of the approach. Highlights: It is proposed a multi-objective control for cooperative payload transport with rotorcraft UAVs based on null-space theory. The proposal allows to set on-line the load weight that each vehicle must transport. Strategies to avoid conflicts of interest between objectives are proposed. Accurate dynamic models for helicopters, flexible cables and payload are used to test the proposal in a realistic scenario. System stability is proven using Lyapunov theory and several simulation results show the good performance of the approach.